Imprementasi Prinsip-Prinsip Bioetika Dalam Pengolahan Dan Pemanfaatan Plant Growth Promoting Rhizobacteria (PGPR): Implementasi Prinsip-Prinsip Bioetika - Simanjuntak, Maretta (Jurnal Biogenerasi, 2024)
The utilization of Plant Growth Promoting Rhizobacteria (PGPR) is a promising solution to enhance plant growth and productivity in a sustainable and environmentally friendly manner. However, the large-scale application of this technology still faces challenges, particularly in ensuring that the processing and utilization of PGPR are conducted with consideration of bioethical principles. This research aims to explore the implementation of bioethical principles such as autonomy, non-maleficence, beneficence, justice, and duty in the context of PGPR processing and utilization. A qualitative approach using literature review, critical analysis, and expert interviews was employed in this study. The research findings identified key challenges such as a lack of understanding of bioethics and limited resources, as well as other constraints such as the importance of using natural materials and ensuring safety for humans, the environment, and other living organisms. The recommendations provided include the development of regulations and best practice guidelines, enhancing transparency and community involvement, investing in PGPR research and development focused on safety, effectiveness, and sustainability, and fostering collaboration among various stakeholders. By integrating scientific and ethical aspects, it is hoped to realize sustainable, environmentally friendly agriculture that benefits the wider communit